PENANGANAN UNMET NEED KB DI KAMPUNG KB: STUDI KASUS DI DUA KAMPUNG KB DI KABUPATEN CIANJUR - Sri Sulastri; Hetty Krisnani; Diah Puspita Sari; Rindang Ekawati (Jurnal Kependudukan Indonesia, 2019)
One of the tasks of Â Kampung KB (Keluarga Berencana) is to reduce the proportion of unmet need for family planning by utilizing family planning field officers and gaining support from related institutions. This study aims to analyze the process of handling the unmet need for family planning in two Kampung KB in Cianjur Regency. The research used a qualitative approach in forms of individual in-depth interviews and focus group discussions. Data are analyzed descriptively based on case studies. The findings indicate that data recording instruments used daily in the research sites have not been able to identify groups of women with unmet need for family planning. Therefore, the existing services of family planning information have not been based on the needs of the target group. After the formation of Kampung KB, family planning information services and contraception services were more vigorous. While all of the services ease couples of childbearing age with unmet need for family planning to get related information and contraception, monitoring and evaluation activities still cannot be carried out because of the unavailability of officers as well as the target group and post-service data. In addition, there is no clear division of labor between the board Kampung KB and other family planning field officers in each stage of the handling of unmet need for family planning.